Mental Health, Social and Emotional Well-Being, and Perceived Burdens of University Students During COVID-19 Pandemic Lockdown in Germany - Kohls, Elisabeth; Baldofski, Sabrina; Moeller, Raiko; Klemm, Sarah-Lena; Rummel-Kluge, Christine (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has been affecting everyone’s daily life in unknown measures since its outbreak. Nearly all universities around the globe were affected. Further, young people and university students in particular, are known to be vulnerable for developing mental disorders. This study aims to examine the mental health social and emotional well-being and perceived burdens of university students during COVID-19 pandemic lockdown in Germany. Materials and Methods: This cross-sectional and anonymous online survey among university students assessed mental health status with standardized measures (depressive symptoms, alcohol and drug consumption, and eating disorder symptoms), attitudes towards the COVID-19 pandemic and perceived burdens, and social and emotional aspects of the pandemic (social support, perceived stress, loneliness, and self-efficacy). Results: In total, N = 3,382 German university students participated. Nearly half of the students (49%) reported that they are worried or very much worried about the COVID-19 pandemic. The majority supports the governmental lockdown measures (85%). A Patient Health Questionnaire-9 (PHQ-9) sum score of 10 or above, indicating clinically relevant depressive symptoms, was reported by 37% (n = 1,249). . The PHQ-9 sum score was on average 8.66 (SD = 5.46). Suicidal thoughts were indicated by 14.5% of the participants. Levels of depressive symptoms differed significantly for the different self-rated income changes during the pandemic (increase, decrease, no change in income). Further, levels of depressive symptoms and suicidal ideation differed significantly for students from different faculties. A multiple regression analysis revealed that not being a parent, having no indirect social contact one or two times a week, higher perceived stress, higher experienced loneliness, lower social support, and lower self-efficacy significantly predicted higher scores of depressive symptoms. Other aspects of lifestyle such as social and cultural activities, dating, and hobbies were reported to be negatively affected during the pandemic. Conclusion: The present study implies that university students are vulnerable and due to elevated depressive symptoms at risk, being hit hard by the pandemic, but are in general coping adaptively. Low-threshold online interventions promoting help-seeking and also targeting various mental health conditions might bridge the gap the COVID-19 pandemic opened up recently.